The Effect of Playing Plasticine on the Fine Motor Development of Children Aged 4-6 Years in Kindergarten - Safari, Ganjar; Al Syurfah, Zein; Yusfar, KM; Pujiastuti, Liana (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Fine motor development in children aged 4-6 years is able to use scissors correctly, write numbers, letters, draw body parts. However, the facts in the field, especially in Widuri Kindergarten, SKB Playschool, Mawar Putih Playschool, there are still many children aged 4-6 years who are not able to hold a pencil properly, have not been able to hold scissors and hold the crayon correctly and even draw body parts are not able to cause problems with children's fine motor development that is slow and causes obstacles to children in completing their tasks. Objective: The purpose of this study was to determine the effect of playing plasticine on fine motor development of children aged 4-6 years kindergarten in Baleendah Village, Bandung Regency. Method: The method used in this study is with experimental methods with Quasi Experimental Design research design. Result and Discussion: The statistical test in this study is Mc Nemar obtained results with p-value (Asymp. Sig 2 tailed) of 0.0001 < 0.05, it can be concluded that there is an effect of playing plasticine on fine motor development in children aged 4-6 years kindergarten in Baleendah Village, Bandung Regency. Conclusion: Through this study there are results that playing plasticine has an influence on children's fine motor development, therefore it is hoped that learning methods by utilizing plasticine play can be applied in kindergartens in Baleendah Village